On the dynamics of water and suspension in the Keret' River estuary (Karelian coast of the White Sea). - Dolotov, Yury S; Kovalenko, V N; Lifshits, V Kh; Petrov, M P; Platonov, A V; Prego, Ricardo; Ratkova, Tatyana N; Filatov, N N; Shevchenko, Vladimir P (PANGAEA, 2002)
In September 2000 we carried out a comprehensive study of dynamics of water and suspension in the area south of the Chupa Bay adjacent to the Keret' Archipelago and the estuary of the Keret' River (Karelian coast of the White Sea) onboard R/V Ekolog. The entire study area can be divided into three estuary zones characterized by different dynamic regimes: marine, intermediate, and near-mouth zones. Autumn stratification of the water column is particularly distinct in the most dynamic marine zone. The strongest mixing of the upper layer is also observed in the marine zone. The most intensive dilution and the largest thickness of the diluted water layer are found in the near-mouth zone. On the whole in the near-mouth zone concentration of suspended matter is higher than in the intermediate and marine zones. The highest phytoplankton abundance is observed in the marine zone, whereas the lowest one is confined to the near-mouth zone. At all the stations both abundance and biomass of flagellates dominate.
Biomass of the most abundant taxons and phytoplankton groups in the Keret' River estuary (White Sea) in September 2000
Keywords: Archive of Ocean Data; ARCOD; Chaetoceros socialis, biomass as carbon, integrated; Choanoflagellates, biomass as carbon, integrated; Chrysomonadina, biomass as carbon, integrated; DEPTH, water; Diatoms, biomass as carbon, integrated; Dinoflagellates, biomass as carbon, integrated; Ek-00-01; Ek-00-05; Ek-00-06; Ek-00-29; Ek-00-B-1; Ek-00-B-2; Euglenophyta, biomass as carbon, integrated; Flagellates indeterminata, biomass as carbon, integrated; Phytoplankton, biomass as carbon, integrated; Picophytoplankton, biomass as carbon, integrated; Prymnesiophyceae, biomass as carbon, integrated; Water sample; White Sea; WS